2012
DOI: 10.6000/1927-3037/2012.01.02.05
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Study of Anticoccidial Activity of Medium Chain Fatty Acids (MCFA) and their Corresponding Monoglycerides on Broiler Chicken Coccidiosis

Abstract: The effect of anticoccidial from oil containing medium chain fatty acids and their corresponding monoglycerides, which known as enhanced virgin coconut oil (EVCO) was investigated. A total of 100 broiler chicks were assigned to four treatment groups. Group A, B and C were infected with 8 species of live coccidia. Group A was then treated with 30% EVCO; Group B with antibiotic (Coccisul-Q) and no treatment for Group C. Group D as control. The birds infected with live coccidia (Group A, B and C) had significantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 6 publications
1
6
0
Order By: Relevance
“…Conversely, other studies showed no broiler performance improvement when birds received MCFAs in comparison with control birds and birds fed antibiotics (Gunal et al, 2006;Vieira et al, 2008). However, at the moment, numerous studies suggest that MCFAs have growth-promoting properties and can be used as alternatives to antibiotics and anticoccidiostats (Tan & Long, 2012;Khan & Iqbal, 2016).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Conversely, other studies showed no broiler performance improvement when birds received MCFAs in comparison with control birds and birds fed antibiotics (Gunal et al, 2006;Vieira et al, 2008). However, at the moment, numerous studies suggest that MCFAs have growth-promoting properties and can be used as alternatives to antibiotics and anticoccidiostats (Tan & Long, 2012;Khan & Iqbal, 2016).…”
Section: Discussionmentioning
confidence: 98%
“…It was reported that Aromabiotic decreased the invasion of enteric pathogens, decreased mortality and had positive effects on growth performance and intestinal histomorphology in broiler chickens (Khosravinia, 2015;Gutierrez et al, 2006) and Japanese quail (Saeidi et al, 2016). Numerous natural products, such as sources of fats containing high concentrations of n-3 fatty acids or feedstuffs, have been tested as anticoccidial dietary additives (Tan & Long, 2012). MCFAs have been found to have anticoccidial activity in calves and antiprotozoal activity in dairy cattle, swine, sheep, goat and infant animals (Tan & Long, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Candida albicans, C. krusei and Pityrosporumovale [18]. A preliminary study of anticoccidial activity of EVCO on broiler chicken coccidiosis showed a promising result with a significant reduction of oocysts level observed in faecal and cecal dramatically after 4 days posttreatment with EVCO [20], which has generally recognized as safe (GRAS) status and it can be a good and safer alternative way to control harmful pathogens. Prevention of new infection is a key strategy for mastitis control and milk quality management handling.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a recent study on the effect of EVCO against coccidiosis in broiler chicken also showed promising results and can be used as an alternative way to control coccidiosis in the poultry industry (Tan and Long, 2012). The present study aims to determine the efficacy of EVCO against three potent mastitis causal agents, namely S. aureus (ATCC 31885), S. agalactiae (ATCC 12927) and S. dysagalactiae (ATCC 27957).…”
Section: Introductionmentioning
confidence: 99%